Transition rather than balance: Organizing constraints for collective creativity in pharmaceutical development - Lukas Vogelgsang (Creativity and Innovation Management, 2020)
When it comes to organizing for collective creativity, management scholars typically advise balancing between constraint and freedom. However, this suggestion to balance is often too enigmatic in practice, neglects the dynamics inherent in creative processes, and predominantly highlights the inhibiting aspects of constraints. Thus, the present article aims to rethink this balancing proposition by asking how constraints unfold during collective creative processes. Based on four cases of pharmaceutical development, it illustrates how collective creativity is enabled by constraints from two distinct sources, namely restraint and contingency. The article further shows how and why these constraint sources alternate along the development trajectory. While constraints can enable collective creativity, phases of constraint transition are eventually necessary to revitalize the development process. Building upon these findings, the article concludes that organizing constraints for collective creativity is a matter of transition rather than balance.
Keywords: 330; collective creativity; constraint; process